2018
DOI: 10.4149/bll_2017_118
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of epinephrine in rats: evaluation by impedance cardiography

Abstract: Tachycardia was detected in the epinephrine group. There was an inverse correlation between LVET and dZmax/dt and IC. This is based on the fact that epinephrine increases inotropic effect (Tab. 2, Fig. 4, Ref. 30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The use of impedance cardiography for hemodynamic measurements may represent another study limitation; this method was shown to potentially over-or underestimate the results during NIV compared to the thermo-dilution method (14). Nevertheless, impedance cardiography is an established non-invasive method to assess hemodynamic functions in both experimental (15) and clinical (16) studies, which is reliable when assessing trends (17).…”
Section: Discussionmentioning
confidence: 99%
“…The use of impedance cardiography for hemodynamic measurements may represent another study limitation; this method was shown to potentially over-or underestimate the results during NIV compared to the thermo-dilution method (14). Nevertheless, impedance cardiography is an established non-invasive method to assess hemodynamic functions in both experimental (15) and clinical (16) studies, which is reliable when assessing trends (17).…”
Section: Discussionmentioning
confidence: 99%
“…The second key parameter triggered by EE was post-resuscitation hypertension. Blood pressure is directly associated with vasoconstriction (α-agonist effect) and cardiac output (β-agonist effect) (14, 46, 47). Therefore, we suspected that early administration might maximize the dual effects (α and β agonist effects) of epinephrine and then ROSC would be easier to establish.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, greater systemic vascular resistance might be detrimental to an end organ by limiting perfusion/cardiac output to that organ. On the other hand, it has been shown that EE provides benefit by increasing coronary artery perfusion pressure, and this might be associated with better outcomes (46, 48). Nevertheless, post-resuscitation oxygenation, rhythm, level of consciousness, body temperature, and urine output were not significantly associated with EE.…”
Section: Discussionmentioning
confidence: 99%